2019
DOI: 10.1080/15592294.2019.1605815
|View full text |Cite
|
Sign up to set email alerts
|

Using NGS-methylation profiling to understand the molecular pathogenesis of young MI patients who have subsequent cardiac events

Abstract: Globally, ischaemic heart disease is a major contributor to premature morbidity and mortality. A significant number of young Myocardial Infarction (MI) patients (aged <55 y) have subsequent cardiac events within a year of their index event. This study used Next Generation Sequencing (NGS) methylation to understand the pathogenesis in this subset of young MI patients, comparing them to a cohort of patients without recurrent events. Cases and controls were matched for age, gender, ethnicity, and comorbidities. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Currently, medications such as aspirin, warfarin, tissue plasminogen activator, and interventional therapy, such as percutaneous coronary intervention (PCI), are the mainstay of treatment for AMI ( Lu et al, 2015 ; Doenst et al, 2019 ; Sabatine and Braunwald, 2021 ). However, unpredictable complications such as bleeding, ischemia/reperfusion injury, and coronary restenosis may occur, highlighting the need for safer and more innovative therapeutic strategies to optimize clinical outcomes ( McCarthy et al, 2018 ; Doenst et al, 2019 ; Mackman et al, 2020 ; Zhang et al, 2022 ).Several studies have observed significant individual methylation differences in patients with MI ( Ek et al, 2016 ; Rask-Andersen et al, 2016 ; Thunders et al, 2019 ; Han et al, 2022 ; Luo et al, 2022 ; Ren et al, 2022 ). Further exploration of the regulatory mechanisms of DNA methylation and its potential impact on metabolism and vascular physiology after MI may help reduce the incidence of post-MI complications ( Ward-Caviness et al, 2018 ).…”
Section: Roles Of Dna Methylation After Myocardial Infarctionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, medications such as aspirin, warfarin, tissue plasminogen activator, and interventional therapy, such as percutaneous coronary intervention (PCI), are the mainstay of treatment for AMI ( Lu et al, 2015 ; Doenst et al, 2019 ; Sabatine and Braunwald, 2021 ). However, unpredictable complications such as bleeding, ischemia/reperfusion injury, and coronary restenosis may occur, highlighting the need for safer and more innovative therapeutic strategies to optimize clinical outcomes ( McCarthy et al, 2018 ; Doenst et al, 2019 ; Mackman et al, 2020 ; Zhang et al, 2022 ).Several studies have observed significant individual methylation differences in patients with MI ( Ek et al, 2016 ; Rask-Andersen et al, 2016 ; Thunders et al, 2019 ; Han et al, 2022 ; Luo et al, 2022 ; Ren et al, 2022 ). Further exploration of the regulatory mechanisms of DNA methylation and its potential impact on metabolism and vascular physiology after MI may help reduce the incidence of post-MI complications ( Ward-Caviness et al, 2018 ).…”
Section: Roles Of Dna Methylation After Myocardial Infarctionmentioning
confidence: 99%
“…Research has demonstrated alterations in the degree of methylation of certain genes in individuals with myocardial infarction ( Ek et al, 2016 ; Rask-Andersen et al, 2016 ; Ward-Caviness et al, 2018 ; Thunders et al, 2019 ), which are associated with cardiac function, cardiogenesis, and recovery after ischemic injury. To understand the early dynamic changes of gene expression after MI, RNA-seq and MeDIP-seq were used on heart tissues from AMI mice at different time points ( Han et al, 2022 ; Luo et al, 2022 ), and the results showed that DNA methylation plays an important role in the pathophysiological progression after MI.…”
Section: Introductionmentioning
confidence: 99%
“…We have used the protocol described here for several human cancers 1 , 2 , 3 , 4 , 5 and have also successfully used it for DNA methylation analysis of other human diseases, 6 , 7 , 8 normal human cells, 9 , 10 mice, 11 zebrafish, 12 , 13 , 14 , 15 and mangrove rivulus. 16 …”
Section: Before You Beginmentioning
confidence: 99%